Characterization of scaffolds for neural tissue engineering - CESUR, SÜMEYYE; ULAĞ, SONGÜL (Elsevier Science, Oxford/Amsterdam, 2023)
With the advancement of tissue engineering techniques, the repair of nerve injuries has acquired a novel dimension. It is now appropriate to establish a scaffold that entirely mimics the biological and mechanical properties of real human tissue using tissue engineering techniques. In order to determine how well synthetic and/or natural polymers can construct optimal scaffolds, cells and growth factors can also be investigated to enhance the functionality of scaffolds. Studies are underway to design biodegradable, biocompatible, electrically conductive, and immunologically inert scaffolds. The primary objective is to accurately simulate the extracellular matrix in the human body and to expose the conjunction of biochemical, topographic, and electrical features employing different polymers, cells, and growth hormones. This chapter focuses on the importance of processing/engineering and characterization techniques for neural tissue scaffolds used to regenerate neural diseases.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)